The Influence of Animated Video Media on Elementary School Students' Motivation and Learning Outcomes in Science Learning - Maulana, Alman; Yuliyanto, Aan; Amanaturrakhmah, Isna (Indonesian Journal of Elementary Education (IJEE), 2025)
The low motivation and learning outcomes of students in learning science are one of the main challenges in efforts to improve the quality of education in elementary schools. This study aims to determine the effect of using animated video media on student motivation and learning outcomes in science subjects. The method used in this research is an experiment with a nonequivalent control group design. The population of this study was all students from one of the elementary schools in Pamulihan District, with a sample consisting of 41 students, namely 18 female students and 23 male students. Data collection techniques used questionnaires, pretest-posttest, observation, and interviews. The results showed that the R-squared value for student learning motivation in the experimental class was 0.041 or 4.1%, with a sig value of 0.393, while in the control class it was 0.313 or 31% with a sig 0.008. For learning outcomes, the R square value in the experimental class was 0.347 or 34.7%, with a sig. of 0.006, while the control class showed an R square value of 0.427 or 42.7%. Based on the results of data analysis, it was concluded that there was an influence of animated videos on students' motivation to learn science by 4.1% and on learning outcomes by 34.7%. Thus, the use of animated video media has an influence on increasing student motivation and learning outcomes, although the contribution is not greater than conventional learning in the context of this study.Keywords:Animated Videos, Learning Motivation, Learning Outcomes